O CUIDADO NUTRICIONAL DA PESSOA COM OBESIDADE NA ATENÇÃO PRIMÁRIA A SAÚDE SOB A PERSPECTIVA DE VIGILÂNCIA ALIMENTAR E NUTRICIONAL EM MATO GROSSO DO SUL - Fabiana Santos Araújo de Oliveira (2024)
Introduction: Obesity is a public health problem in Brazil and worldwide, presenting a multifactorial etiology influenced by genetic, metabolic, cultural, social, and behavioral factors, leading to a significant impact on quality of life. The state of Mato Grosso do Sul still lacks an organized flow for the care of overweight and obese patients in the form of a care pathway. Objective: Analyzing the care for overweight/obesity in the state of Mato Grosso do Sul from the perspective of Food and Nutritional Surveillance (FNS). Methods: A questionnaire was administered to healthcare professionals in the state within the scope of Primary Health Care to gather information on the capacity and structure of care in the Unified Health System (SUS) for people with overweight/obesity. Professionals from across the state were questioned about human resources, infrastructure, practices, actions, and programs for obesity care in their territory. Data collection was conducted in partnership with and with the authorization of the State Department of Health (SES) of Mato Grosso do Sul. Data were analyzed by chisquare test to examine differences between the group of professionals who did or did not perform Food and Nutritional Surveillance (FNS) in their daily practice, and between the group of municipalities that maintained or did not maintain multiprofessional teams in Primary Health Care (PHC) to support the Family Health Team (FHT). Results: Municipalities that reported practicing FNS are 40.18% (n=45), and 59.82% (n=67) reported "No" to practicing FNS. The group not performing FNS did not mention conducting "Study of the determinants and conditions of food and nutritional problems in the territory" under any circumstances. It was observed that professionals who performed FNS referred more to group actions related to care for overweight/obese individuals at the Basic Health Unit/Family Health Unit (p=0.040) and mentioned more referrals to other actions at intersectoral action points (p=0.034). In the OR analysis, it was observed that the absence of FNS decreases the chance of offering Integrative and Complementary Practices (ICP) (OR= 3.78; 95%CI 1.29–11.05), knowing referral flows (OR= 2.99; 95%CI 1.40–6.37), conducting food consumption assessment (OR=3.72; 95%CI 1.48–9.32), and offering individual care for overweight/obesity (OR= 3.70; 95%CI 1.06–12.94). Conclusion: Data analysis indicates evidence that FNS can favor a more cohesive flow of overweight and obese patients in PHC, particularly when analyzed from the perspective of maintaining multiprofessional teams. Therefore, maintaining teams and implementing FNS practice in the territory of Mato Grosso do Sul are necessary for the viability of the LCSO.